Novel blue fluorescent materials for high-performance nondoped blue OLEDs and hybrid pure white OLEDs with ultrahigh color rendering index. (February 2020) - Liu, Futong; Liu, Hui; Tang, Xiangyang; Ren, Shenghong; He, Xin; Li, Jinyu; Du, Chunya; Feng, Zijun; Lu, Ping
Abstract: Pure blue luminogens that can be applied in high-efficiency nondoped blue organic light-emitting diodes (OLEDs) and act as main component to generate white OLEDs with high color rendering index (CRI) simultaneously are rarely reported. Herein, two blue emitters, TPAATPE and PPIATPE, consisting of triphenylamine/phenanthroimidazole and tetraphenylethene-substituted anthracene with asymmetric structures are designed and synthesized. The nondoped OLED using TPAATPE as the emitter exhibits pure blue emission with the maximum external quantum efficiency (EQE) of 6.97% and Commission International de L'Eclairage (CIE) coordinates of (0.15, 0.16). Employing TPAATPE as the blue-emitting component, combined with a thermally activated delayed fluorescent (TADF) molecule PTZMes2 B, which is adopted as the green emitter and the host for phosphors to modulate the long wavelength emission, a series of highly efficient hybrid white OLEDs are successfully achieved. Among them, the two-color white OLED exhibits eye-friendly warm white light with a maximum forward-viewing EQE of 25.2%. In particular, the three-color white OLED achieves pure white emission with CIE coordinates of (0.34, 0.38), a maximum forward-viewing EQE of 25.3% and an ultrahigh CRI of 92. All of nondoped blue OLEDs and hybrid white OLEDs exhibit very small efficiency roll-offs with excellent color stabilities. To the best of our knowledge, these results are among the best outcomes for white OLEDs reported so far. Graphical abstract: By adopting TPAATPE as the blue-emitting component, thermally activated delayed fluorescent molecule PTZMes2 B as the green emitter as well as the host for long-wavelength phosphors, the target devices can achieve external quantum efficiencies exceeding 25% in two-color warm white OLED and three-color pure white OLED with ultrahigh CRI of 92. Image 1 Highlights: The nondoped OLED based on TPAATPE exhibits pure blue emission with a maximum EQE of 6.97% and CIE of (0.15, 0.16). At the luminance of 1000 cd m −2, the EQE can still remain as high as 5.96%, demonstrating a small efficiency roll-off. The two-color WOLED yields an eye-friendly warm white light with a maximum forward-viewing EQE of 25.2%. The three-color WOLED is obtained by utilizing incomplete energy transfer between host PTZMes2 B and guest Ir(piq)3 . The three-color WOLED achieves pure white light with a maximum forward-viewing EQE of 25.3% and an ultrahigh CRI of 92.